Explanation of the Causal Model of Digital Leadership Based on Information Culture on Information Literacy of History Teachers in Salah al-Din Province, Iraq - Hameed Majeed, Fouad; Omidian, Faranak; Dheyab Abed, Qays; Baratali, Maryam (Assessment and Practice in Educational Sciences, 2024)
The present study was conducted with the aim of presenting an “Explanation of the Causal Model of Digital Leadership Based on Information Culture on the Information Literacy of History Teachers in Salah al-Din Province, Iraq.” The statistical population of the study included all history teachers in Salah al-Din Province, Iraq, totaling 200 individuals. Based on Cochran’s sample size formula, 127 teachers were selected as the statistical sample. Participants responded to a researcher-made questionnaire on digital leadership based on information culture and the information literacy questionnaire developed by Davarpanah (2009). The results of the thematic analysis indicated 14 organizing themes, each of which more precisely covered different dimensions of digital leadership. These organizing themes included: a knowledge-based cultural context, transparent and accountable leadership, continuous organizational learning, trust-based cohesion, integration of information systems, advanced knowledge-oriented technologies, dynamic and flexible structures, system-based transparency, valuing organizational knowledge, convergence of culture and knowledge, innovation as culture, collective organizational participation, organizational accountability, and culture-centered transformation. In total, 56 basic themes were extracted from the interviews, each uniquely and non-redundantly adding detail and depth to the organizing and overarching themes. These basic themes comprehensively covered various aspects of digital leadership based on information culture and contributed to a more holistic understanding of the research topic. In the quantitative phase, using statistical methods and structural equation modeling (SEM), the effect of digital leadership based on information culture on the information literacy of history teachers was examined. The quantitative results demonstrated that digital leadership grounded in information culture has a direct and significant effect on the information literacy of history teachers.